2007
DOI: 10.4321/s0365-66912007000900007
|View full text |Cite
|
Sign up to set email alerts
|

Incisiones limbares relajantes y cirugía de la catarata: nuestra experiencia

Abstract: RESUMENObjetivo: Evaluar la reducción del astigmatismo corneal preexistente en la cirugía de catarata mediante incisiones limbares relajantes (ILRs). Método: Estudio prospectivo de dos grupos de pacientes (tratamiento y control) con astigmatismo prequirúrgico ≥1D. Los 30 pacientes del grupo control fueron sometidos a facoemulsificación por incisión temporal en córnea clara y los 32 pacientes del grupo tratamiento a ILRs junto a facoemulsificación por incisión temporal en córnea clara. Se usó el test de Hollada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
(3 reference statements)
0
3
0
Order By: Relevance
“…8 However, the amount of astigmatism that can be corrected and the predictability and stability of the correction are controversial. [8][9][10][11][12] Moreover, studies of recently introduced toric IOLs 13-17 show them to be a promising option with excellent outcomes. Given the improvement in the rotational stability of toric IOLs, 13,14 it is import to ascertain whether the results exceed those with conventional incision techniques.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…8 However, the amount of astigmatism that can be corrected and the predictability and stability of the correction are controversial. [8][9][10][11][12] Moreover, studies of recently introduced toric IOLs 13-17 show them to be a promising option with excellent outcomes. Given the improvement in the rotational stability of toric IOLs, 13,14 it is import to ascertain whether the results exceed those with conventional incision techniques.…”
mentioning
confidence: 99%
“…It is estimated that approximately 50% of the population older than 60 years has more than 1.00 diopter (D) of astigmatism 1 and that up to 22% of cataract surgery candidates have preexisting astigmatism exceeding 1.50 D. [2][3][4] Although not firmly established, the level of cylindrical defect that can be considered clinically significant is approximately 0.50 to 1.00 D. 5 Treatment options to address preoperative astigmatism include positioning or enlarging the main incision, performing astigmatic keratotomy, [6][7][8][9][10][11] creating opposite clear corneal incisions, using laser ablative procedures, and implanting a toric intraocular lens (IOL). 12-17,A In eyes with low to moderate astigmatism, creating peripheral corneal relaxing incisions, also known as limbal relaxing incisions, is one of the most widespread techniques.…”
mentioning
confidence: 99%
“…[8][9][10] Coloma-González I et al reported LRI as a safe as well as an effective way to reduce any pre-existing astigmatism during cataract surgery and importantly it provides good unaided visual acuity. 10 Lim R et al further evaluated the long term stability of keratometric effects of LRI and reported that the keratometric effects of LRI were stable at 10 weeks to 3 years after the surgery. 11 Sharma and Kumar study evaluated LRI when done along with cataract surgery and concluded that LRI can reduce preoperative astigmatism effectively and with a good predictability of the angle.…”
Section: Discussionmentioning
confidence: 99%